SISTEM INFORMASI PENJUALAN BERBASIS WEB DENGAN METODE WATERFALL PADA PT FASTRATA BUANA JAKARTA: Information System, Sales, Website, SDLC - Nuraeni, Nia; Sa’id, Nur (LP2M Universitas Nurdin Hamzah, 2020)
Competition in the corporate world to force every person pursuing a strategy to increase its business. Strategy adopted also vary according to type of effort to gain market share as much as possible. One of the advances in information technology has become fundamental in creating a marketing strategy is the e-commerce. To facilitate ease of transactions and business operations at the company then needs to be made web-based sales system (booking online) that can save time, especially in the delivery or exchange of information (data, sample product images, etc.), ordering products and transactions can be done anywhere any time by customers in various regions. SDLC (System Development Life Cycle)method is the method used tp design this website.